2012
DOI: 10.1002/smll.201200381
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐Induced Exosomes Target Antigen‐Presenting Cells to Initiate Th1‐Type Immune Activation

Abstract: The mechanisms associated with the induction of systemic immune responses by nanoparticles are not fully understood, but their elucidation is critical to address safety issues associated with the broader medical application of nanotechnology. In this study, a key role of nanoparticle-induced exosomes (extracellularly secreted membrane vesicles) as signaling mediators in the induction of T helper cell type 1 (Th1) immune activation is demonstrated. In vivo exposure to magnetic iron oxide nanoparticles (MIONs) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 34 publications
2
77
0
Order By: Relevance
“…In particular, in those individuals who already have pre-existing allergic conditions (known as sensitised individuals), the generated exosomes may result in a delayed type of hypersensitivity reaction and subsequent severe allergic responses; whereas in unsensitised individuals, the resulting immune activation response may be much lower. Furthermore, a key role of nanoparticle-induced exosomes as signalling mediators in the induction of immune activation via T helper cell type 1 has been reported [129]. Taken together, these studies suggest that the generated exosomes aggravate the immune activation and inflammatory responses induced by exposure to nanoparticles.…”
Section: Pitfalls Conclusion and Perspectivessupporting
confidence: 53%
“…In particular, in those individuals who already have pre-existing allergic conditions (known as sensitised individuals), the generated exosomes may result in a delayed type of hypersensitivity reaction and subsequent severe allergic responses; whereas in unsensitised individuals, the resulting immune activation response may be much lower. Furthermore, a key role of nanoparticle-induced exosomes as signalling mediators in the induction of immune activation via T helper cell type 1 has been reported [129]. Taken together, these studies suggest that the generated exosomes aggravate the immune activation and inflammatory responses induced by exposure to nanoparticles.…”
Section: Pitfalls Conclusion and Perspectivessupporting
confidence: 53%
“…Zhu et al [90] reported that exposure to magnetic iron oxide nanoparticles results in significant exosome generation in the alveolar region of Balb/c mice. Through exosome-initiated signals, immature DCs were found to undergo maturation and differentiation, while macrophages were activated and differentiated to the M1 subtype.…”
Section: Nanomaterials and The Adaptive Immune Systemmentioning
confidence: 98%
“…They were quickly translocated into system circulation, stimulated the maturation of dendritic cells, and activated Th1-type immune response. 85,155 This mechanism may account for the long-term inflammatory effects associated with nanoparticle exposure 156 and suggests that the control of immune signal transduction via exosomes may minimize the adverse immune responses caused by the inhaled nanoparticles. An IL-1a mediated molecular mechanism has also been proposed.…”
Section: 152mentioning
confidence: 99%